Webdocumentário, documentário interativo: A produção documental interativa no suporte digital - Souza, Lorene Dias de (2017)
Interactive documentary production in digital media, recognized as webdocumentary and also as interactive documentary, can be considered as another evolution of the documentary tradition, a new milestone in the history of the documentary in the face of its expansion on the Internet with the emergence of new digital technologies and media convergence. The virtual environment enabled unique formats for the production and content of documentary narratives, transforming them into non-linear and interactive works and with their experimentation supported by the exploration of multimedia resources organized in digital support. This research sought to clarify this new interactive production in two ways, one starting from a possible trajectory of the traditional linear documentary film to the interactive nonlinear documentary to highlight the main characteristics that surround the genres. On the other, identifying propositions that would allow to understand the different types of interactive documentary and webdocumentaries. The concepts of documentary approach and navigation dynamics and interaction modes were analyzed and applied in an isolated and joint way in examples of foreign and brazilian works, which allowed to recognize different attributes of the productions that define this new interactive documentary genre.